Subfamily Heteromyzinae newly recorded from China with description of one new species (Diptera: Heleomyzidae) - Zeng, Wei; Xu, Xingnong; Yang, Ding (Zootaxa, 2023)
This study reported the subfamily Heteromyzinae with its genus Tephrochlamys from China for the first time. Tephrochlamys Loew is a small genus in Heteromyzinae with only 13 known species from the Afrotropical, Oriental, Palaearctic and Nearctic Regions. Here, we described one new species of Tephrochlamys from Qinghai of Palaearctic China: Tephrochlamys qinghaiensis sp. nov. An updated key to the Palaearctic species of Tephrochlamys is presented.